The book of Numbers : a critique of Genesis - Carmichael, Calum M. (Yale University Press, 2012)
In this work Calum Carmichael--a legal scholar who applies a literary approach to the study of the Bible--shows how each law and each narrative in Numbers, the least researched book in the Pentateuch, responds to problems arising in narrative incidents in Genesis. The book continues Carmichael's process of demonstrating how every law in the Pentateuch is a response to a problem arising in a biblical narrative, not to an inferred societal situation.